2021
DOI: 10.3390/vetsci8010008
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality Effects on the Mineral Profile of Goats Farmed in the Semiarid Region of Brazil

Abstract: Seasonality effects on the mineral profile of goats were evaluated. Fifty males were divided into two groups, one with mineral supplementation and one control. Seasonal evaluation was conducted during four periods: beginning, middle, and end of the dry period and middle of the rainy period. Rib and liver biopsies were performed, and blood was collected at each period to evaluate mineral accumulation. Ca, P, Cu, Fe, Mo, Zn, and Co concentrations were determined using inductively coupled plasma optical emission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…Zn and Cu concentration (ppm) and BCS of Bligon does with inactive or active ovariesThe serum Zn levels of Bligon goats in this study ranged from 0.99 to 5.16 ppm. This value was comparable to the results of studies on Nubian goats of 1.12-6.59 ppm(Hamid et al, 1994), goats in Kashmir of 0.86 ± 0.21 ppm(Yatoo et al, 2013), and goats in Austria of 0.27-1.09 ppm(Schweinzer et al, 2017), but higher than the blood Zn levels of goats in Brazil of 0.54-0.66 ppm(Lima et al, 2021), Kacang goats in West Sumatra of 0.37 ± 0.16 ppm(Khalil et al, 2019), and Saanen goats in Iran of 0.59 ppm(Samimi et al, 2021). Overall, the serum Zn levels of Bligon does in the recent study were above the critical level (de ciency) recommended for goats byMcDowell (1985) and cited by Goklaney et al (2018), namely 0.80 ppm.…”
supporting
confidence: 88%
“…Zn and Cu concentration (ppm) and BCS of Bligon does with inactive or active ovariesThe serum Zn levels of Bligon goats in this study ranged from 0.99 to 5.16 ppm. This value was comparable to the results of studies on Nubian goats of 1.12-6.59 ppm(Hamid et al, 1994), goats in Kashmir of 0.86 ± 0.21 ppm(Yatoo et al, 2013), and goats in Austria of 0.27-1.09 ppm(Schweinzer et al, 2017), but higher than the blood Zn levels of goats in Brazil of 0.54-0.66 ppm(Lima et al, 2021), Kacang goats in West Sumatra of 0.37 ± 0.16 ppm(Khalil et al, 2019), and Saanen goats in Iran of 0.59 ppm(Samimi et al, 2021). Overall, the serum Zn levels of Bligon does in the recent study were above the critical level (de ciency) recommended for goats byMcDowell (1985) and cited by Goklaney et al (2018), namely 0.80 ppm.…”
supporting
confidence: 88%
“…The synergistic and complementary activity of the aforementioned parameters enhances to some extent the lifelong production and well-being of farm animals [ 45 ]. Various studies have profiled the hemato-biochemical variations in different breeds of goats in different geographical areas [ 16 , 18 ] [ 17 ]. Nevertheless, Shiba goats—a non-seasonal breeding goat that is reared principally in Japan [ 1 , 46 ], supports lifelong research studies in animal reproduction [ 1 , 36 ], and has been recently introduced in cardiovascular pathophysiology [ 2 , 3 , 4 , 10 ]—have not been investigated before.…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of mineral elements and their roles in oxidative stress are essential as a complementary tool in the evaluation of the nutritional and metabolic status of animals. Several studies have demonstrated the link between nutritional status, oxidative stress markers, and changes in organ and tissue contents of some mineral elements at normal and deficient levels concerning puberty onset, impaired reproductive efficiency, reproductive seasonality, growth rate, milk production, and mortality of goats and their kids [ 12 , 15 , 16 , 17 ]. The first few months of an animal’s life are critical because they determine the performance style and the economic trait of the individuals; hence, more benefits would be obtained when earlier puberty and sexual maturity, which are ultimately under the control of reproductive hormones.…”
Section: Introductionmentioning
confidence: 99%
“…Mineral supplementation, mainly zinc, is indicated during the dry period. Zinc bioavailability in ruminants appear to be affected by dietary factors that have not yet been clearly defined [ 45 ].…”
Section: Discussionmentioning
confidence: 99%